How can we develop a more clinically useful and robust algorithm for diagnosing and treating nocturia? ICI‐RS 2017. (31st July 2018) - Everaert, Karel; Hervé, François; Bower, Wendy; Djurhuus, Jens C.; Dmochowski, Roger; Fine, Noam; Wein, Alan; Wyndaele, Michel; Weiss, Jeffrey
Abstract : Aims: Nocturia, or waking up at night to void, is a highly prevalent and bothersome symptom. Currently, there is a lack of clear and consistent recommendations regarding evaluation and management of nocturia. The aim of this report is to discuss how to fill the gaps in our knowledge in order to develop a practical patient‐oriented diagnostic and therapeutic algorithm for nocturia. Methods: This paper is a report of the presentations and subsequent discussion of a Think Tank session at the annual International Consultation on Incontinence Research Society (ICI‐RS) in June 2017 in Bristol. Results and Conclusion: Further investigations are needed to better understand the pathophysiology of nocturia, to allow improvement in diagnosis, and to optimize treatment by increasing efficacy and reducing adverse events. Patient‐oriented practical guidelines on nocturia are needed to help clinicians from different disciplines diagnose and treat nocturia.